CHANGE MANAGEMENT PROCESS AND LEADERSHIP STYLES - Akinbode, Akintola Ismaila; Al Shuhumi, Said Rashid Ali (PEOPLE: International Journal of Social Sciences, 2018)
In today VUCA (Volatile, Uncertain, Complex and Ambiguous) world, every organization or institution is susceptible to change wave. Any organization that fails to positively respond to change will surely go to extinction. However for successful initiation and implementation of change initiatives, there is need for diligence and skillfulness from the part of organizational leaders especially those from Higher Education Institutions (HEIs). Several studies have confirmed that seventy percent of change initiatives fail and the failure has been largely attributed to leaders’ ineffectiveness in anchoring change programme. Through extensive analysis of findings of several case studies, failure to gradually institutionalize change initiatives and inappropriate leadership styles are found to be part of the reasons why change initiatives fail in Higher Education Institutions (HEIs). This paper therefore discusses change management process and leadership styles. Turning institutions to learning organization and adoption of transformational leadership style are recommended for effective change management process.